PERBUDAKAN DAN PEMBUNUHAN TERHADAP TAWANAN PERANG : Membandingkan Pemikiran Imam Abu Suja Dalam Kitab Taqrib dan Hukum Humaniter Internasional - Andi Purwono (Jurnal Iqtisad, 2020)
The relationship between international humanitarian law and Islam has been extensively written. The major similarities and the minor differences between the two have already been mentioned. This paper tries to analyze the incompatibility between the two in the context of prisoners of war. One of popular classical book (kitab kuning) in Indonesia pesantren (islamic boarding school) is Taqrib or Ghayatul Ikhtishar (very short explanation) written by Imam Abu Suja. The chapter of jihad of this fiqh (syariah/ islamic law) book, descript the status of men, women, and children arrested in conflict. Slavery and Murdery of these arrested ones made controversial issue. These two things are certainly contrary to international humanitarian law. To understand his thinking, it is a need to broaden the reading to some syarah (books explaining) the taqrib.